The epidemiological effect and cost-effectiveness of expanded age eligibility for recombinant zoster vaccination in England. - Ku,C-C; Rosello,A; Walker,J; Pouwels,KB; Baguelin,M; Davies,NG; Jit,M (Vaccine, 2026)
INTRODUCTION: Since September 2023, England's national immunisation programme has offered the recombinant zoster vaccine (RZV) to adults aged 65-79 as a preventative measure against shingles (herpes zoster) and its complications. However, adults aged 80 and over are currently not eligible for the vaccine. We aimed to evaluate the feasibility and cost-effectiveness of providing RZV to adults aged 80 and older in England. METHODS: This cost-utility analysis employs a static cohort model considering herpes zoster (HZ) cases and severe cases leading to post-herpetic neuralgia, HZ-related hospitalisation, and deaths from the perspective of the National Health Service. The long-term impacts of RZV are assessed using the model, accounting for changing population demographics and the previously-offered live zoster vaccine (ZVL). We consider different eligibility scenarios for RZV focusing on the older population (80+ years old) and provide comparisons to the pre-2023 programme. RESULTS: Expanding the current programme to offer a single dose of RZV to people aged 80 and up is likely to be cost-effective relative to the current programme. Offering two doses to this group would be less cost-effective but would offer greater protection against HZ. For preventing health-related quality of life loss, it is most efficient to vaccinate 60-69-year-olds, but for averting hospitalisation costs, it is most efficient to vaccinate 80-89-year-olds. CONCLUSION: Providing one or two doses of RZV for older adults can be cost-effective and would reduce the healthcare burden of shingles.